INTERSUBJEKTIVITAS WAJAH DAN TANGGUNG JAWAB HUMANITER: MENYIKAPI AMORALITAS PERANG - Simon Pedro Pitang; F. X. Eko Armada Riyanto; Mathias Jebaru Adon (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The research focuses on exploring the meaning of Emanuel Levinas' ethics of face in illuminating the immorality that occurs in war. For Levinas, humans are